Characterisation of cobalt, aluminium, and magnesium-promoted MoVTeNbOₓ catalysts synthesised by microwave-assisted slurry method for propane oxidation to acrylic acid - Wong, Hong Ren (2017)
The selective oxidation of propane to acrylic acid is potential to replace the current manufacture of acrylic acid which uses propene as feedstock, due to this light alkane is more abundant and lower cost. Up to date, the most promising catalyst that has been reported for this selective oxidation of propane is MoVTeNbOx metal mixed oxide, yet its’ performance does not achieve the requirement of being commercialised. Thus, aseries of metal-promoted MoVTeNbOx catalysts (MVTN-A, where A = Co, Al, Mg) were synthesised by microwave-assisted slurry method, and then followed by calcination in air at 553 K for 1 hour and then in nitrogen at 873 K for 2 hours. It appears that the as-synthesised samples were semi-crystalline Anderson-type structure. Once calcined, the phase transformed into mixed phases of orthorhombic M1 phase, hexagonal M2 phase and tetragonal (V0.07Mo0.93)5O14 phase. Only when the samples were port-treated in hydrogen peroxide, the evolution of orthorhombic M1 phase was observed. Since there is no appreciable formation of orthorhombic M1 phase was obtained, the calcined catalysts were post-treated in 30 % hydrogen peroxide. The physicochemical properties of the catalysts were examined using X-ray Diffraction (XRD), Fourier-Transform Infrared (FT-IR), Brunauer-Emmett-Teller (BET) surface area measurement, Field Emission Scanning Electron Microscopy (FESEM) and Temperature Programmed Reduction in hydrogen (H2-TPR). Characteristics of the as-synthesised, calcined and post-treated catalysts were obtained. According to XRD results, highly pure orthorhombic M1 phase, Te2M20O57 (M = Mo, V or Nb), was formed when MoVTeNbOx was promoted with 0.06 mole of Mg, 0.02 mole of Al, or 0.10 mole of Al. An increase in specific surface area could be seen in those promoted with magnesium and aluminium, as compared to the un-promoted MoVTeNbOx (13.4 m2/g). On contrary, the specific surface area of cobalt-promoted catalysts was close to the un-promoted catalyst. Temperature Programmed Reduction in hydrogen (H2-TPR) results indicated the enhanced reducibility of the cobalt-, aluminium- and magnesium-promoted catalysts as opposed to the unpromoted ones, signifying the apparent high activity of the catalyst. The propane conversion increased as follow: MVTN < MVTN-Al(0.02) < MVTN-Al(0.10) < MVTN-Mg(0.06). The selectivity of acrylic acid, however, progressively rose in this order: MVTN-Al(0.02) < MVTN < MVTN-Al(0.10) < MVTN-Mg(0.06). Among the tested catalysts, MVTN-Mg(0.06) gave the highest propane conversion (49.9 %) and acrylic acid’s selectivity (34.9 %). Meanwhile, for aluminium promoted MoVTeNbOx, the higher propane conversion and selectivity of acrylic acid is found for higher loading of metal promoter.